2018
DOI: 10.1177/0308022618808735
|View full text |Cite
|
Sign up to set email alerts
|

Supporting the participation of youth with physical disabilities: Parents' strategies

Abstract: Introduction: Little is known about strategies used by parents to explicitly promote the participation in meaningful occupations of transition-age youth. This descriptive study explored the type and scope of parents' strategies to facilitate the participation of youth living with a physical disability. Methods: Twenty-two parents of youths (12 to 18 years) with mobility restriction reported strategies used at home, school, and in the community by completing the Participation and Environment Measure for Childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…Motivation and focus over this 4-week baseline may also have been facilitated by the biweekly check-ins from the therapist asking parents to rate their child's current performance for each goal. During this phase, parents demonstrated the ability to independently come up with solution-based environmental strategies that were effective, as found in other studies [ 46 , 47 ]. Further studies should include a larger, more socially diverse group of parents in terms of family functioning, while monitoring the specific strategies used by parents.…”
Section: Discussionsupporting
confidence: 56%
“…Motivation and focus over this 4-week baseline may also have been facilitated by the biweekly check-ins from the therapist asking parents to rate their child's current performance for each goal. During this phase, parents demonstrated the ability to independently come up with solution-based environmental strategies that were effective, as found in other studies [ 46 , 47 ]. Further studies should include a larger, more socially diverse group of parents in terms of family functioning, while monitoring the specific strategies used by parents.…”
Section: Discussionsupporting
confidence: 56%
“… Riklin et al (2019) highlighted the need to address the social and sociopolitical environment for children and youth with facial differences, which caregivers of youth with physical disabilities have also emphasized in their strategies for promoting their children’s participation ( Killeen et al, 2018 ). Killeen et al (2018) showed a high prevalence of participation-focused strategy use by caregivers that targeted their child’s school environment, including advocacy and collaboration with school staff. Because the PEM–CY yields data on caregiver strategy use, additional analyses of these data will help to identify common ways in which specific barriers to school participation are being addressed among children with CFM ( Johns et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although the overall strategy scope was broad, nearly half of caregiver strategies targeted the extrinsic participationrelated construct, that is, the child's environment or context. Similarly, the environment has been reported on as a primary focus in prior studies examining children's participation in an educational setting (Benjamin et al, 2017;Killeen et al, 2019) as well as among caregivers of children with physical disabilities or surviving critical illness (Jarvis et al, 2018;Killeen et al, 2019). Together, these findings reinforce the importance, and familiarity, of environmentally focused strategies to families when supporting a young child's participation across multiple settings and regardless of diagnosis.…”
Section: Unpacking Complexity To Design Participation-focused Early Interventionmentioning
confidence: 52%